Leptin expression is substantially correlated with prognosis of urinary bladder carcinoma. Issue 1 (1st January 2021) - Khabaz, Mohamad Nidal; Qureshi, Imtiaz Ahmad; Al-Maghrabi, Jaudah Ahmad
ABSTRACT: This study examined leptin expression in cases of bladder cancer and its diagnostic and prognostic usefulness in bladder malignancies. A set of 128 urinary bladder cancer cases and 24 normal specimens of bladders were employed for an immunohistochemical investigation of leptin expression in tissue microarrays. Leptin was up-regulated during transformation and was identified as brown cytoplasmic granules in the malignant urothelium of 123 (96%) bladder neoplasms, of which 68 (53.1%) cases showed high levels (moderate to strong) of staining. Strong staining was found to be associated with high stages (P = 0.001), muscularis propria infiltration (P < 0.001), vascular invasion (P < 0.03), lymph node involvement (P < 0.02), metastases (P < 0.05), and mortality (P < 0.03). Furthermore, various important survival distributions were detected with leptin expression in the malignant urothelium (P < 0.03). These pilot results suggest that leptin might be a valid marker for predicting the stage and bad prognoses in bladder carcinoma.